The Maqashid Sharia Perspective on Women's Involvement in Supporting Family Livelihoods in Jantho City - Sabil, Jabbar; Fazira, Nisa (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
Employing women outside the home to meet the needs of the family can provide benefits, but it can also cause mafsadat to the family and the woman herself, both in the context of maintaining religion (hifz al-din) and maintaining the soul (hifz al-nafs). The benefits are private so they tend to be subjective, while the mafsadat that is possible to arise is public so that it can be objectified intersubjectively. This requires the ability to weigh the potential of mafsadat based on the conditions and situations experienced. This is the reason why research with problem formulation is important; The criteria for maslahat-mafsadat in women's involvement in fulfilling family support. The researcher combines descriptive social research methods with prescriptive legal research methods through a method called al-ijtihad al-maqashidi. It was found that there were various benefits including those at the primary level, and there were efforts from respondents to minimize the effects of mafsadat. It was also found that the social system at Jantho Market is still within the boundaries of manners and there is no quiet place that has the potential for khalwat to occur. In addition, female traders do not do activities at night to avoid a time when crime is vulnerable. This research concluded that the activities of women traders in Jantho Market have been in line with the rules of maqashidiyyah. However, mutual awareness and cooperation are needed to anticipate the potential of mafsadat.